2018
DOI: 10.1002/jcp.27908
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of Sonic Hedgehog signaling pathway in gastric mucosa of rats with MNNG‐induced gastric precancerous lesions

Abstract: Objective To explore the changes of Sonic Hedgehog (Shh) signaling pathway in the stomach mucosa during the formation of gastric precancerous lesions. Methods A total of 72 suckling rats in half genders were randomly and equally divided into the normal group and model group. The rats in the model group were administered with 0.1 ml 1‐methyl‐3‐nitro‐1‐nitrosoguanidine (MNNG) at the dosage of 800 mg/L for 10 days, whereas the rats in the normal group were similarly administered with normal saline. A total of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…N-Methyl-N′-nitro-N-nitrosoguanidine (MNNG)-induced mouse model, one of the chemical carcinogenesis models, has been widely used for the GC and development of gastric precancerous lesions ( Cai et al, 2018 , 2019 ; Xu et al, 2018 ; Zhang et al, 2018 ; Zhao et al, 2019 ). In this study, we modified the MNNG-induced model to combined with sodium salicylate drinking, ranitidine feed, and irregular diet (multifactor induction) that were used to simulate the main factors leading to chronic gastritis and GC such as irregular diet, gastric mucosal inflammation damage, and PPI abuse to establish PLGC rat model regarding our previous report ( Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…N-Methyl-N′-nitro-N-nitrosoguanidine (MNNG)-induced mouse model, one of the chemical carcinogenesis models, has been widely used for the GC and development of gastric precancerous lesions ( Cai et al, 2018 , 2019 ; Xu et al, 2018 ; Zhang et al, 2018 ; Zhao et al, 2019 ). In this study, we modified the MNNG-induced model to combined with sodium salicylate drinking, ranitidine feed, and irregular diet (multifactor induction) that were used to simulate the main factors leading to chronic gastritis and GC such as irregular diet, gastric mucosal inflammation damage, and PPI abuse to establish PLGC rat model regarding our previous report ( Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…MNNG is typically used to construct a GPL animal model because it has the advantages of high stability and easy administration[ 11 ]. In this experiment, GPL was successfully induced in rats by a compound modeling method of drinking MNNG freely in the dark + 20% ethanol/hot saline-ranitidine by alternating gavage + alternating "satiation-starvation" (Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…The expressions of Shh, Smo, Gli-1, and Cyclin D1 mRNA in gastric mucosa increase in varying degrees. Smo activates downstream transcription factor Gli and initiates the transcription of many target genes ( 7 ). Knocking out the Smo gene, as a key signaling transduction molecule of the Hh signaling pathway, will block the Hh signaling pathway in rat embryos ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it’s generally believed that PLGC is irreversible and that the main purpose of the treatment is for the eradication of Helicobacter pylori , acid inhibition, the protection of the gastric mucosa, and symptomatic treatment ( 6 ), but the effect is not significant. Studies have shown that the hedgehog (Hh) signaling pathway in patients with PLGC is abnormally activated and has a specific expression in the process of the occurrence and development of PLGC ( 7 ).…”
Section: Introductionmentioning
confidence: 99%